Reduction of Masticatory Neurons in the Tooth Extracted and Aged Mouse - Rashid, Mohammed Enamur; Akhter, Khaleda; Maeda, Norihiko (Bangladesh Journal of Anatomy, 2013)
Bangladesh Journal of Anatomy, January 2012, Vol. 10 No. 1 pp 37-42 DOI: http://dx.doi.org/10.3329/bja.v10i1.15758